IMPLEMENTATION OF KUNTOWIJOYO'S PROPHETIC SOCIAL SCIENCES AS AN APPROACH TO RECONSTRUCT THE INTERPRETATION OF THE QUR’ANIC VERSES OF THE STORY OF IBRAHIM - Daib Insan Labib, Muhammad Alfreda; Nurhaedi, Dadi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This study explores the utilization of Kuntowijoyo's concept of Prophetic Social Science as a method for comprehending the verses of the Qur'an. The passages in question pertain to the narrative of Abraham engaging in dialogue with different interlocutors. This study addresses three key inquiries: 1) The definition of ISP and Kuntowijoyo's perspective on it. 2). Which passages pertain to the narrative of Ibrahim AS? 3). What is the process of constructing verse interpretation through ISP and how do the implications and implementations of interpretation products affect social life in Indonesia. The research methodology employed is descriptive analysis, specifically utilizing a literature review technique encompassing primary materials authored by Kuntowijoyo and secondary sources published by other scholars who have explored Kuntowijoyo's concepts. The findings of this study indicate that ISP, which stands for Islamic Science Prophetic, is a scientific output derived from prophetic material that encompasses more than only the teachings of Prophet Muhammad. 2). Ibrahim serves as an exemplary character that may be emulated as a role model in ISP. This is derived from the manner in which Ibrahim engaged in discussion with his interlocutors. 3). Ibrahim's dialogue approach serves as an exemplary model for fostering peace in social life, particularly among religious individuals in Indonesia.Tulisan ini membahas tentang bagaimana konsep Ilmu Sosial Profetik Kuntowijoyo dijadikan sebagai sebuah pendekatan dalam memahami ayat-ayat al-Qur’an. Adapun ayat-ayat yang dimaksud adalah ayat yang berkaitan dengan kisah dialog Ibrahim dengan berbagai lawan bicara. Kajian ini berangkat dari tiga pertanyaan mendasar, 1). Apa yang dimaksud dengan ISP dan bagaimana pemikiran Kuntowijoyo. 2). Apa saja ayat-ayat yang berkaitan dengan kisah Ibrahim AS. 3). Bagaimana kontruksi interpretasi ayat melalui ISP dan bagaimana pula implikasi serta implementasi produk interpretasi dalam kehidupan bermasyarakat di Indonesia. Metode penelitian yang digunakan adalah deskriptif analitik, khususnya dengan menggunakan pendekatan kajian kepustakaan melalui sumber-sumber primer karya Kuntowijoyo maupun sumber-sumber sekunder yang dituliskan orang lain terkait ide-ide Kuntowijoyo. Hasil penelitian ini adalah 1). ISP adalah produk ilmu yang diambil dari data profetik kenabian yang tidak hanya terpaku kepada nabi Muhammad. 2). Ibrahim merupakan figur yang dapat dijadikan role model dalam ISP. Hal ini didasari dari bagaimana Ibrahim berdialog dengan lawan bicaranya. 3). Konsep dialog Ibrahim adalah contoh yang ideal bagi umat manusia, khususnya umat beragama di Indonesia dalam menciptakan kedamaian dalam kehidupan sosial.